ANALISIS MINAT KERJA DAN PROGRAM MAGANG TERHADAP KESIAPAN KERJA (STUDI TERHADAP MAHASISWA STIE INDONESIA BANKING SCHOOL) - Sastra, Muh. Punggawa Rizha; Nuraya, Ahmad Setiawan (Ibs Press, 2025)
Work readiness is crucial in preparing human resources for the sustainability of the industry, efforts need to be made to obtain optimal results, in order to improve the research, the objects used as research materials are students of STIE Indonesia Banking School batch 2019 and 2020, with the title of the research